The effects of Video Tutorial Screencast SketchUp Make (VTS-SUM) in learning 3D geometry for low achievers - Yahya, Faridah Hanim (Horizon Research Publishing, 2020)
Problems in learning 3D geometry are related to students’ spatial abilities that require them to create mental images representatives of the objects. Studies had shown that 3D software should be incorporated into teaching in order to assist students in visualizing. However, students often exhibit difficulties when using it as they are not familiar with tools and could not remember steps in completing a task. The purpose of the study is to examine the effect of a learning strategy which uses video tutorial screencast SketchUp Make (VTS-SUM) for topic plan and elevation, in mathematics for upper secondary school in Malaysia. The videos were designed using ADDIE Model which integrated screencast technique with a 3D software (SketchUp Make). A total of 30 low achiever students from one secondary school were involved in this study. They watched the video tutorials and performed hands-on activities using the software to complete the tasks. This paper includes a report of a usability test which used a seven point Likert scale. The questionnaire consists of four constructs: usefulness, ease of use, ease of learning and satisfaction. The findings showed that all means were at high level and the highest mean was satisfaction. Furthermore, pre- and post-test were also administered to students. The results of the paired sample t-test revealed that, there were significant differences in the mean scores of pre- and post-test, before and after learning via VTS-SUM (t=-4.30; p<0.05). Thus, we can conclude that VTS-SUM can be a potential learning strategy that enhances students’ achievement in 3D geometry.